Comparison of the effect of W-shaped and linear skin incisions on scar visibility in bilateral external dacryocystorhinostomy - Yazici B (Dove Medical Press, 2015)
Bulent YaziciDepartment of Ophthalmology, Uludag University, Bursa, TurkeyThe article entitled "Comparison of the effect of W-shaped and linear skin incisions on scar visibility in bilateral external dacryocystorhinostomy" by Ekinci et al1 was published in Clinical Ophthalmology; I reviewed this paper for another journal (Journal of Ophthalmology) several months ago before it appeared in your journal.It seems that the authors submitted their rejected paper to your journal, after making some unethical, methodological changes. View the original paper by Ekinci et al